STRATEGI PEMBELAJARAN AL QUR’AN METODE UMMI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL QUR’AN SANTRI PONDOK PESANTREN ISLAM AT TAUHID SURABAYA - Moch. Abdulloh Sattar; Ely Masnawati; Sulchan Ghazali (Hijri, 2026)
This study aims to describe the Qur'an learning strategy using the Ummi Method and analyze its effectiveness in improving the Qur'an reading skills of santri at Islamic Boarding School At Tauhid Surabaya. The Ummi Method is a Qur'an learning method that emphasizes the direct method, repetition, and affection with the principles of being easy, enjoyable, and touching the heart.This research used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included Ummi Method teachers and santri of Islamic Boarding School At Tauhid Surabaya. The results showed that the Ummi Method Qur'an learning strategy is implemented through 7 basic stages: opening, apperception, concept planting, understanding, drill/skill, evaluation, and closing.The implementation of the Ummi Method has proven to improve santri's Qur'an reading skills, marked by: 1) Improved reading fluency according to tajwid rules, 2) Improved accuracy of makhraj and letter characteristics, 3) Increased motivation and enjoyment of santri in learning the Qur'an. Supporting factors for success include certified teacher competence, the Ummi Foundation quality management system, and consistency in using the jilid books. The inhibiting factors are the differences in santri's initial abilities and limited learning time.Keywords: Learning Strategy, Ummi Method, Qur'an Reading Skills